Bryozoa (Cyclostomata and Ctenostomata) from polymetallic nodules in the Russian exploration area, Clarion–Clipperton Fracture Zone, eastern Pacific Ocean—taxon novelty and implications of mining - Grischenko, Andrei V.; Gordon, Dennis P.; Melnik, Viacheslav P. (Zootaxa, 2018)
This work describes Bryozoa of the orders Cyclostomata and Ctenostomata found associated with polymetallic nodules collected by box-coring in the eastern part of the Russian exploration area of the Clarion-Clipperton Fracture Zone (CCFZ) under contract to Yuzhmorgeologiya. Scanning electron microscopic study of 358 cyclostome colonies and 14 ctenostome colonies from 4510–5280 m depth has resulted in the recognition of two new species of Ctenostomata, and 14 new species, nine new genera and two new families of Cyclostomata; three additional species of Cyclostomata are left in open nomenclature pending the discovery of missing reproductive characters. The taxonomic novelty is thus notable. One of the new Ctenostomata represents the first living example of the previously monotypic Late Cretaceous genus Pierrella. Twelve of the new cyclostome taxa have well-developed gonozooids, indicating that embryonic cloning (polyembryony) is normal in this deep-sea environment. On the other hand, one indeterminate tubuliporine and two rectangulates have dimorphic peristomes. In the latter two cases, enough mature colonies were found to suggest that this feature is normal, and that the dimorphic zooids are possibly female—in other words, capacious incubation chambers are apparently lacking, and therefore polyembryony would also be lacking or reduced. In one of these species, evidence is presented to suggest that the ancestrular zooid can reproduce precociously. Of the species reported here, only one has previously been found outside the exploration area, highlighting both the limited knowledge we have of bryozoans in the deep Pacific and/or a fauna that is largely endemic to the nodule environment. An additional 31 species of Cheilostomata have also been discovered that will be described in a subsequent publication. Most bryozoans are macrofaunal-sized, so are both inadequately determinable and overlooked in images obtained by remotely operated vehicles; yet, with 50 species, Bryozoa is the most speciose sessile macrofaunal phylum on the nodules. Nodules constitute hard substrata in an area otherwise mostly inhospitable for Bryozoa, hence mining would lead to loss of critical habitat. Further, as suspension-feeders, bryozoans are highly susceptible to smothering by suspended sediment, and non-mined areas closely adjacent to extraction zones would likely also be affected and their associated bryozoan fauna obliterated. More data are required on the distribution of the CCFZ bryozoan species elsewhere in the east Central Pacific to determine if mining would lead to local taxon extirpation or global extinction at both low and high taxonomic levels.